A meta-analysis reveals the protein profile associated with malignant transformation of oral leukoplakia - Normando, Ana Gabriela Costa; dos Santos, Erison Santana; Sá, Jamile de Oliveira; Busso-Lopes, Ariane Fidelis; De Rossi, Tatiane; Patroni, Fábio Malta de Sá; Granato, Daniela Campos; Guerra, Eliete Neves Silva; Santos-Silva, Alan Roger; Lopes, Márcio Ajudarte; Paes Leme, Adriana Franco (Frontiers in Oral Health, 2023)
The search for biomarkers associated with oral leukoplakia malignant transformation is critical for early diagnosis and improved prognosis of oral cancer patients. This systematic review and meta-analysis aimed to assess protein-based markers potentially associated with malignant transformation of oral leukoplakia. Five database and the grey literature were searched. In total, 142 studies were included for qualitative synthesis, where 173 proteins were investigated due to their potential role in malignant progression from oral leukoplakia (OL) to oral squamous cell carcinoma (OSCC). The abundance of these proteins was analyzed in fixed tissues and/or biofluid samples, mainly by immunohistochemistry and ELISA, and 12 were shared by both samples. Enrichment analysis revealed that the differential abundant proteins are mostly involved with regulation of cell death, regulation of cell proliferation, and regulation of apoptotic process. Also, these proteins are mainly expressed in the extracellular region (55.5%), cell surface (24.8%), and vesicles (49.1%). The meta-analysis revealed that the proteins related to tumor progression, PD-L1, Mdm2, and Mucin-4 were significantly associated with greater abundance in OSCC patients, with an Odds Ratio (OR) of 0.12 (95% CI: 0.04 – 0.40), 0.44 (95% CI: 0.24 – 0.81), and 0.18 (95% CI: 0.04 – 0.86), respectively, with a moderate certainty of evidence. The results indicate a set of proteins that have been investigated across OSCC initiation and progression, and whose transcriptional expression is associated with clinical characteristics relevant to the prognosis and aggressiveness. Further verification and validation of this biomarkers set are strongly recommended for future clinical application.